TANGGUNG JAWAB PENYEDIA PLATFORM USER GENERATED CONTENT (UGC) ATAS KERUGIAN KONSUMEN SESUAI KITAB UNDANG-UNDANG HUKUM PERDATA - Simatupang, Estomihi FP (E-Journal Widya Yustisia, 2020)
The implementation of electronic systems in User Generated Platform (UGC) (platform users) consumers as platform users can experience losses due to the failure of the platform's electronic system. This is an illegal act by traders on the platform. Losses due to unlawful acts are leaking of user's personal data due to illegal actions by merchants who provide the goods / services offered. The purpose of this study is to discuss the liability under civil law of platform providers in the form of user generated content for consumer losses (case study of the Tokopedia platform), development contributions to consumer protection law in online transactions. The method used in this research is juridical normative by conducting library research in the form of legislation and literature related to the problem under study. The case of the leakage of personal data of Tokopedia users is a legal relationship between consumers and a user generated content platform provider and a legal relationship between electronic system users and electronic system administrators based on government regulation No. 82 of 2012 which has been amended by Government Regulation No. 71 of 2019.